REPRODUCTIVE SYSTEM IN FULL-TERM AND PRETERM NEWBORN GIRLS - Svetlana I.yelgina; Galina A. Ushakova; Elena N. Nikulina (Фундаментальная и клиническая медицина, 2016)
Aim: To assess the reproductive system in preterm and full-term newborn girls. Materials and Methods: We recruited full-term and preterm newborn girls (58 and 42, respectively) and collected umbilical cord serum samples. Results: We measured the indicators of physical development, somatic health, vulvar anatomy, and ovarian reserve. Expectedly, we noted statistically significant differences between the preterm and full-term newborn girls. Conclusion: Premature birthaffects the reproductive system in the antenatal period.